Electrochromic Polycationic Organoboronium Macrocycles with Multiple Redox States. Issue 33 (5th July 2021) - Shimoyama, Daisuke; Baser‐Kirazli, Nurcan; Lalancette, Roger A.; Jäkle, Frieder
Abstract: Polycationic macrocycles are attractive as they display unique molecular switching capabilities arising from their redox properties. Although diverse polycationic macrocycles have been developed, those based on cationic boron systems remain very limited. We present herein the development of novel polycationic macrocycles by introducing organoboronium moieties into a conjugated organoboron macrocyclic framework. These macrocycles consist of four bipyridylboronium units that are connected by fluorene and either electron‐deficient arylborane or electron‐rich arylamine moieties. Electrochemical studies reveal that the macrocycles undergo reversible multi‐step redox processes with transfer of up to 10 electrons. Switchable electrochromic behavior is demonstrated via spectroelectrochemical studies and the observed color changes are rationalized by correlation with computed electronic transitions using DFT methods. Abstract : Polycationic organoboronium macrocycles comprising four bipyridylboronium units in a cyclic conjugated framework are introduced, with the boron cations linked by fluorene and two electron‐deficient arylborane or two electron‐rich arylamine moieties. Cyclic voltammetry and spectroelectrochemical studies reveal that multiple redox states can be reversibly accessed with transfer of up to 10 electrons and switchable electrochromic properties are realized.